Regulation of Periplasmic Carbonic Anhydrase Expression in Chlamydomonas reinhardtii by Acetate and pH. - Fett, J. P. (1994)
The effects of mixotrophic growth with acetate and growth medium pH on expression of extracellular carbonic anhydrase (CA) in Chlamydomonas reinhardtii were evaluated. Addition of 10 mM acetate to the culture medium resulted in reduction of CA activity that was parallel to the reduction generated by growth of the algae in high external CO2 concentrations. This reduction in activity is a consequence of lower level of the CA protein as determined by western analysis. Transcript abundance of cah-1, the gene encoding the low CO2-induced CA, is also reduced by the addition of acetate as verified by northern analysis. Measurements of photosynthesis and respiration suggest that the acetate-induced reduction of CA expression is not a function of lowered photosynthetic capacity, but may be the result of increased internal CO2 concentration generated by high, acetate-stimulated respiratory rates. Growth medium pH can also influence extracellular CA expression. The induction of CA activity, protein abundance, and transcript levels by exposure to limiting inorganic carbon (Ci) concentrations is much more pronounced at higher than at lower pH values. The relationship between pH regulation of CA expression and its role in the Ci-concentrating mechanism are discussed.